There is nothing so practical as a good theory social psychology and social development issues in the Philippine context. [article]. - Intal, A. Miren Gonzalez .
This papeer presents various ways by which social psychological theories and concepts can be usefully applied towards solving problems related to national development. The discussion focused on problems in human development, resource and productivity, and institutional development.